2020
DOI: 10.1093/mnras/staa1946
|View full text |Cite
|
Sign up to set email alerts
|

The 2MASS redshift survey galaxy group catalogue derived from a graph-theory based friends-of-friends algorithm

Abstract: Abstract We present the galaxy group catalogue for the recently-completed 2MASS Redshift Survey (2MRS, Macri et al.2019) which consists of 44572 redshifts, including 1041 new measurements for galaxies mostly located within the Zone of Avoidance. The galaxy group catalogue is generated by using a novel, graph-theory based, modified version of the Friends-of-Friends algorithm. Several graph-theory examples are presented throughout this paper, including a new method… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 82 publications
0
16
0
Order By: Relevance
“…In order to mitigate the effect of the fingers-of-god in the reconstruction, we use the corresponding galaxy group catalog of Tully (2015), placing galaxies at the mean redshift of their associated group. Other group catalogs are available (e. g. Lim et al 2017;Lambert et al 2020), but we prefer Tully (2015) because it is also used in the grouping of CF3 galaxies, thus ensuring an optimal match between redshift positions in both 2MRS and CF3. Galaxies with negative redshifts and those outside of the reconstruction volume, 𝑠 > 𝑟 max , are excised.…”
Section: Mrsmentioning
confidence: 99%
“…In order to mitigate the effect of the fingers-of-god in the reconstruction, we use the corresponding galaxy group catalog of Tully (2015), placing galaxies at the mean redshift of their associated group. Other group catalogs are available (e. g. Lim et al 2017;Lambert et al 2020), but we prefer Tully (2015) because it is also used in the grouping of CF3 galaxies, thus ensuring an optimal match between redshift positions in both 2MRS and CF3. Galaxies with negative redshifts and those outside of the reconstruction volume, 𝑠 > 𝑟 max , are excised.…”
Section: Mrsmentioning
confidence: 99%
“…1, spectra and redshifts of the galaxies in the field of 24P73 are not contained in any 2MASS redshift surveys (2MRS) (e.g. Lambert et al 2020). Furthermore, they are not listed in HI-surveys of objects in the ZoA: neither in the Nancay HI Zone of Avoidance survey of 2MASS bright galaxies (Kraan-Korteweg et al 2018), nor in the catalogue of EBHIS HI-detected galaxies in the northern ZoA (Schröder et al 2019b).…”
Section: Spectroscopymentioning
confidence: 99%
“…For example, it has been demonstrated that the Milky Way disk obscures the central part of the dynamically important Great Attractor region (Dressler et al 1987) as well as the Perseus-Pisces Superclus-ter (Giovanelli & Haynes 1982). In the recent years, more comprehensive catalogues of galaxies in the ZoA were produced: the 2MASS redshift survey (2MRS; Macri et al 2019;Lambert et al 2020) and the Zone of Avoidance catalogue of 2MASS bright galaxies (see Schröder et al (2019a) and references therein). The 2MRS aims to map the three-dimensional distribution of an allsky flux-limited sample of~45 000 galaxies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In any event, group finding algorithms have to negotiate these radial fingers, disentangle and reconstruct the true distribution of galaxies 5 . To understand and mitigate these velocity biases, a new graph-theory visualisation based method was developed in the IVL (Lambert et al, 2020). It essentially draws a line between two galaxies (or "friends") with a weighting (represented with line weight, or a distinct color) that may be used to identify strong linkages (or friends) and weak ones, as well as sub-groupings (groups within groups); see Fig 10.…”
Section: All-sky Redshift Survey Explorationmentioning
confidence: 99%